Patient‐Reported Quality of Life After Resection With Primary Closure for Oral Tongue Carcinoma. (7th May 2020) - Ochoa, Edgar; Larson, Andrew R.; Han, Mary; Webb, Katherine L.; Stanford‐Moore, Gaelen B.; El‐Sayed, Ivan H.; George, Jonathan R.; Ha, Patrick K.; Heaton, Chase M.; Ryan, William R.
Abstract : Objectives/Hypothesis: For early‐stage oral tongue carcinoma and carcinoma in situ (ESOTCCIS), we evaluated patient‐reported quality‐of‐life (QOL) outcomes following resection with primary closure (R‐PC). Study Design: Retrospective review at an academic cancer center. Methods: Thirty‐nine ESOTCCIS patients (Tis, T1, T2) who underwent R‐PC without radiation completed the University of Washington Quality of Life Questionnaire Version 4 (UW‐QOL) at least 6 months since R‐PC (mean = 2.39 years; range = 0.5–6.7 years). We compared UW‐QOL scores for pain, swallowing, chewing, speech, and taste to established normative population scores. Multivariable regression analysis evaluated factors associated with QOL impairment. Results: ESOTCCIS patients who underwent R‐PC in comparison to the normative population reported significantly worse mean speech (87.7 vs. 98, P  < .001) and taste (85.6 vs. 95, P = .002) scores and no significant differences in mean pain (91.7 vs. 86, P = .96), swallowing (100 vs. 98, P = .98), chewing (97.4 vs. 94, P = .98) scores. For speech and taste, 59% (23/39) reported no postoperative change from baseline, whereas 41% (16/39) and 35.9% (14/39) reported mild impairment, respectively. Overall, postoperative QOL was reported as good, very good, or outstanding by 87.2% (34/39). Higher American Society of Anesthesiologists class, cT1 compared to CIS, and ventral tongue involvement were independently associated with worse speech. Age < 60 years was independently associated with worse taste. Conclusions: ESOTCCIS patients who undergo R‐PC without radiation can expect long‐term swallowing, chewing, and pain to be in the normative range. Although a majority of patients can expect to achieve normative speech and taste outcomes, R‐PC carries the risks of mild speech and/or taste impairments. Level of Evidence: 4 Laryngoscope, 131:312–318, 2021